Introduction to therapeutic counseling : voices from the field - Kottler, Jeffrey A. (Australia : Thomson-Brooks/Cole, 2004)
This work provides an overview of therapeutic counselling. The authors emphasise the development of a professional identity, ethical standards, process skills, the therapeutic relationship, personal theory building and understanding meaningful research.
Includes bibliographical references and index.
Keywords: Counseling